Guanidine hydrochloride-induced denaturation of bovine serum albumin: a comparative study and analysis using different probes - Abd. Halim, Adyani Azizah; Abdul Kadir, Habsah; Saad, Tayyab (Malaysian Journal of Science, 2008)
The denaturation of bovine serum albumin (BSA) by guanidine hydrochloride (GdnHC1) showed a single-step, two-state transition, when monitored by different probes such as intrinsic fluorescence at 338 and 333 nm after excitation at 280 and 295 nm respectively, UV difference spectral signal at 288 nm, 1-anilinonaphthalene-8-sulphonate (ANS) fluorescence at 470 nm after excitation at 380 nm, bromophenol blue (BPB)-induced difference spectral signal at 619 nm and A.,„„ of positive difference spectral signal of BPB-BSA complex. A comparison of the denaturation curves obtained with the above mentioned probes showed differences in the requirement of GdnHC1 concentration• for the transition to start and complete. The values for the mid-point of denaturation transition and free energy change associated with GdnHC1 denaturation (AG Du2o.) also varied from each other, using different probes.